Persepsi Mahasiswa Terhadap Praktikum Biologi Umum Jurusan Tadris Biologi Fakultas Tarbiyah Dan Ilmu Keguruan IAIN Kerinci - Emayulia Sastria; Tri Susanti; Devie Novallyan; Prangki Alim Alfatwa (Symbiotic: Journal of Biological Education and Science, 2020)
One way to evaluate general biology practicum is to know the students' perceptions of general biology practicum. This study aims to determine student perceptions of general biology practicum, general biology practicum planning, facilities and infrastructure of general biology practicum, and also to determine the perceptions of students towards the implementation of general biology practicum majoring in biology IAIN Kerinci. This research belongs to the category of qualitative research. To get the data the researcher used the study (1) Observation, observed the general Biology practicum, (2) Interview, semester 1 student lecturer and department head, (3) Documents, data about vision and mission department, and general Biology practicum guide. The results obtained based on the results of data analysis and discussion can be concluded (1) Perception of the General Biology practicum planning Department of Biology Tadris IAIN Kerinci is quite good. (2) Perception of the first semester biology student of IAIN Kerinci regarding the facilities and infrastructure of general biology practicum namely practicum guide is still incomplete and inadequate. (3) The first semester biology student IAIN Kerinci's perceptions regarding the implementation of general boiology practicum, firstly in each practicum the teaching assistant is still not right to use the strategy properly. Second, the media displayed is good, and also for the practicum schedule it has been said on schedule.